The protective effects of etomidate against interleukin-1β (IL-1β)-induced oxidative stress, extracellular matrix alteration and cellular senescence in chondrocytes. Issue 1 (1st January 2022) - Yin, Miaomiao; Xu, Yinmei
ABSTRACT: Osteoarthritis (OA) is a common chronic inflammatory disease associated with aging. Etomidate is an intravenous anesthetic with profound antioxidant and anti-inflammatory effects. We speculated that etomidate might exert a beneficial effect on OA. Herein, we explored the effects of etomidate on interleukin-1β (IL-1β)- induced chondrocytes. Our results prove that etomidate ameliorated the IL-1β-induced oxidative stress in C28/12 chondrocytes by decreasing and increasing the reactive oxygen species (ROS) and glutathione peroxidase (GPx) levels, respectively. Etomidate prevented the IL-1β-induced increase in the expressions of matrix metalloproteinase-3 (MMP-3) and matrix metalloproteinase-13 (MMP-13) in C28/I2 chondrocytes at both mRNA and protein levels. It also caused a significant reduction in the percentage of senescence-associated-β-galactosidase (SA-β-Gal)‐stained chondrocytes, while inducing elevated telomerase activity in IL-1β-treated C28/I2 chondrocytes. The expression levels of senescence regulators, plasminogen activator inhibitor-1 (PAI-1) and p16, were also inhibited by etomidate in IL-1β-treated C28/I2 chondrocytes. In addition, etomidate caused the activation of Adenosine 5ʹ-monophosphate (AMP)-activated protein kinase (AMPK), along with upregulated expression levels of phosphorylated AMPKα and phosphorylated acetyl-Co A carboxylase (ACC). Moreover, blockage of AMPK using compound C abolished the protective effects of etomidate on IL-1β-challenged C28/I2 chondrocytes. Taken together, these results demonstrate that etomidate protected C28/I2 chondrocytes from IL-1β-induced oxidative stress, ECM degradation, and cellular senescence via activating AMPK signaling.